Analysis of Factors Influencing the Use of Accounting Information in Small and Medium Enterprises at Palembang - Aldo Pirando; Harsi Romli; RM. Rum Hendarmin (International Journal of Community Service & Engagement, 2023)
This study aims to determine the analysis of factors affecting the accounting information utilization on small and medium enterprises in Palembang. The population in this study was the MSME manager of Palembang City. The sample collection method utilized Simple Random Sampling. The final total respondents were 100. The data were analyzed by descriptive statistical methods, validity tests, reliability tests, classical assumptions, and multiple regression analysis. The results of the study indicate that several factors influence the use of accounting information in small and medium businesses in Palembang, namely business scale has a significant effect on the use of accounting information. Then the age factor of the company, education, and accounting training also affect the use of accounting information. This research is expected to assist MSME to consider the factor that affects use the Accountant Information Application